Metode Tikitiki Dalam Pembelajaran Perkusi Drum Band Pare Kediri - Mantaaba Zukhruf Nabilunnuha; Sunarto; Wahyu Lestari (Universitas Negeri Surabaya, 2022)
The Tikitiki rhythmic syllable method is a notation reading method developed by Dr. Pono Banoe. This method is an effective method for understanding rhythm for beginners. The success of the practice process of drummer Bahana Eka Sapta is due to the members who have various musical experiences. In addition, the many contributions of drummer Bahana Eka Sapta in fulfilling ceremonies, parades and competitions are an effective factor in the Tikitiki method chosen during practice. The purpose of this study is to analyze how the Tikitiki method is applied in the Bahana Eka Sapta training process. In this study using descriptive qualitative methods. Sources of data taken in this study are primary data sources from members of Bahana Eka Sapta and trainers Bahana Eka Sapta. Meanwhile, secondary data sources were taken when the research took place in the form of documentation, song archives, and assignment letters. Data obtained through observation, interviews and documentation. The results showed that there was ease in understanding the members of the Bahana Eka Sapta drum band after the Tikitiki rhythmic syllable method was applied in the training process so that it became a solution to overcome diverse musical experiences and help new members in understanding rhythm. The Tikitiki method can also be applied to drum band activities at school and institutional extracurricular activities to make it easier for beginners to understand the rhythm of the song.